MENINGKATKAN HASIL BELAJAR MATEMATIKA PADA MATERI PENJUMLAHAN DAN PENGURANGAN BILANGAN DENGAN MENGGUNAKAN BENDA - BENDA KONKRET PADA KELAS 1 DI SD NEGERI 060857 MEDAN TEMBUNG - Azis Sukma; Mandra Saragih; Siti Hadijah (STKIP Subang, 2024)
Mathematics is an important subject in the educational curriculum, and understanding basic mathematical concepts at an early level is the key to success in the next stage. The aim of this research is to improve students' learning abilities in operationalizing addition and subtraction of numbers with the help of concrete objects in grade 1 students at SD Negeri 060857 Medan Tembung. This research uses a type of classroom action research (PTK). Class action research is action research carried out in the classroom that concerns class problems. The data collection methods used are observation, tests for each cycle and documentation. This classroom action research was carried out in two cycles, each cycle consisting of planning, implementation, observation and reflection. The results of the research show that the use of concrete learning media can improve student learning outcomes as seen in cycle I of mathematics subjects from 24 students who completed 9, 15 students and incomplete, with a percentage of 38%, did not meet the minimum threshold for classical completion, then in cycle II, 17 students out of 24 students completed and 7 students who did not complete with a percentage of 70% met the minimum threshold for completion.